The Effect of Some Macroeconomic Variables on the Performance Indicators of Companies Listed on The Tehran Stock Exchange During Sanction Periods (before and after the JCPOA) - Hashem Manzar Zade; Mohammad Reza Abbaszadeh; Reza Hesarzade; Seyed Saeed Malek Sadat (Iranian Journal of Accounting, Auditing & Finance)
This study aims to investigate the effect of some macroeconomic variables on the performance indicators of companies listed on The Tehran Stock Exchange (selected industries) during sanction periods (before and after the Joint Comprehensive Plan of Action). This research is an applied and correlated study using deductive-inductive reasoning. Collected data is analyzed (financial reports). Therefore, this study is ex post facto. The sample of this study was collected over 11 years, spanning from 2010 to 2020, and included 181 firms listed on the Tehran Stock Exchange. Multivariate linear regression is conducted to test the hypotheses. The findings indicate that sanctions (both pre-and post-JCPOA) acted as moderators in the relationship between exchange rate fluctuations and firms’ added value. Except for the automotive industry, sanctions (pre-and post-JCPOA) moderated the relationship between foreign investment and corporate investment activities in all industries. Sanctions (pre-and post-JCPOA) moderated the relationship between the production price index and corporate profitability in all industries except the automotive industry. Sanctions (pre-and post-JCPOA) moderated the relationship between the import of raw materials for intermediate and capital goods and corporate operational activities. America’s withdrawal from Iran's nuclear deal, JCPOA, in 2018 caused great damage to Iran’s economy. These sanctions are expected to have a more destructive impact on business enterprises in the post-JCPOA era. Testing the hypotheses, the results show that sanctions (pre-and post-JCPOA) moderated the relationship between the exchange rate fluctuations and corporate performance indicators. This research provides valuable insight into the sanction conditions and companies’ reactions. It leads companies towards self-sufficiency and cooperation with knowledge-based firms for development and growth and reduces dependence on foreign resources and goods.